Perbandingan Sistem Hukum Negara Indonesia dan Malaysia Mengenai Perlindungan Anak - Firly Ajurni; Novilia Wulan Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to compare the legal framework for child protection in Indonesia and Malaysia. Child protection is an important aspect in social development and community welfare. In this context, a comparison between these two countries provides valuable insights into child protection approaches, policies and implementation. From the research results, it appears that both countries have serious efforts to protect children's rights. However, there are differences in legal approaches and implementation of child protection policies. In Indonesia, there are regulations governing child protection, such as Law Number 23 of 2002 concerning Child Protection, while in Malaysia, there is the 2001 Childhood Act which regulates children's rights. Apart from that, the comparison also covers practical aspects in the implementation of child protection, including child protection programs implemented by the government and related institutions. From the results of this research, it can be concluded that although both countries are committed to child protection, there are differences in legal approaches and implementation of child protection policies. This research provides valuable insights for policy makers, legal practitioners and other stakeholders in efforts to improve child protection in both countries. With a deeper understanding of the differences and similarities in the legal framework for child protection, it is hoped that more effective and comprehensive child protection efforts can be created in the future.